RANCANGAN KAPAL UDARA (AIRSHIP) UNTUK VIDEO MONITORING DARI UDARA - Sugiarmadji HPS; Robertus Heru T; Setiadi; Ediwan (BRIN Publishing, 2003)
Remotely controlled non rigid helium airship type is chosen in airship design criteria for video monitoring. The design consists of airship dimensions and volume determination, maximum take of weight (MTOW) and W (weight empty plus payload) calculations, weight and structures analysis, airship stabilization analysis, airship guidance system, power plant system, position monitoring system, material and process, and payload systems. Here, Helium gas will be filled for generating a lift that is equal to the weight of the displaced air. An Airship Demonstrator Model LPN-01 is built to represent the design results. The model has length of L=8.5 m and 2.2 m diameter, so that the envelope volume is of 20 m. This Demonstrator Model will be used for studying capability or performance of airship, especially on ascent and descent manuever, airship's stability, position monitoring and payloads.